Dynamics of ultrafast dissociation of hydrogenic molecules by resonant antibonding core electron excitation: Conclusions from detuning dependence of H+- kinetic energy distributions from condensed films - NAYDENOV, BORISLAV GEORGIEV (Elsevier, 2011)
The ultrafast dissociation dynamics of condensed water and ammonia by resonant core electron excitations have been studied by measuring the kinetic energy distributions of H+-ions desorbed by [N1s]4a1 and [O1s]4a1 excitations as a function of detuning, ?h?, from the center of the resonance. While the most probable ion energy varies monotonically with ?h? for both systems, the centers of gravity of the kinetic energy distributions are minimal at resonance and shift to higher kinetic energy with detuning to either lower or higher h?. This behavior is explained by contributions from bond evolution processes before and after the core hole decay.
PUBLISHED
Keywords: Physical chemistry; condensed films